The Role of Marriage Agreements in Enhancing Family Welfare: A Maqasid Syari'ah Perspective in Islamic Education - Ahmad, T. Rusli; Husti, Ilyas; Aslati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
This study examines the role of marriage agreements in promoting family welfare within the framework of Maqasid Syari'ah. The research aims to explore how these agreements protect spousal rights, ensure fairness in wealth distribution, and enhance emotional and psychological security, contributing to marital harmony and family stability. Using a qualitative library research method, the study analyzes relevant legal texts, Islamic family law, and existing scholarly literature on marriage agreements. The findings indicate that marriage agreements, when aligned with Maqasid Syari'ah, effectively safeguard the rights of both spouses, promote financial fairness, and foster emotional security by setting clear expectations and responsibilities. The study also highlights the role of marriage agreements in preventing conflicts and ensuring long-term family welfare by providing a structure for conflict resolution and mutual respect. This research contributes to the understanding of how Maqasid Syari'ah principles can be applied to modern marital dynamics, offering a practical framework for improving marital stability and promoting gender equality within the family. The study suggests that marriage agreements should be encouraged as a proactive tool for reducing marital disputes and ensuring equitable relationships in line with Islamic values.